(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is one of the key factors that influences the definition of entrepreneurial women and helps to realize the potential and awareness of existing entrepreneurship characteristics in women. In today’s developing world, it is important that companies and people’s approach are very careful in solving social problems. Entrepreneurship is thought to be the most effective tool in increasing its market share. Social business is one of the key solutions to global challenges such as poverty reduction, employment growth and social reintegration. This study, aimed at the sustainability of women entrepreneurs engaged in social activities in Azerbaijan, has examined the effect of education on how well informed women are and the main factors driving them to this field. For this purpose, the entrepreneurship and social management of women were examined theoretically and systematically. The role of education in women entrepreneurship and the effect of education levels and educational activities of women entrepreneurs in the field of social entrepreneurship in Azerbaijan were examined, as well. Finally, proposals were made on the basis of theory, world experience and analysis.